Mobile Phone-Based Invertebrates Encyclopedia for Elementary School Students - Nur Kumala, Farida; Agus Setiawan, Dwi; Susilo, Edy; Amin, Mohammad; Gipayana, Muhana (International Journal of Engineering and Technology, 2018)
Nowadays, invertebrates have not been widely discussed and included as encyclopedia that may lead to enrich students’ knowledge and the available online encyclopedia language has not matched children’ characteristics. The study was aimed to develop a playstore-based encyclopedia application for elementary school students. The subjects of the study were 124 fifth graders of elementary school students that were randomly chosen from 3 elementary schools in Malang Regency, 3 teachers and 3 experts in content, media, and language. The data were collected through questionnaire and observation. The process of development of mobile phone based encyclopedia was carried out through several steps including need analysis, development encyclopedia design, and result validation. It was found from the study that mobile-phone based (playstore) encyclopedia is considered as an effective, interactive, and interesting means by elementary schools students that can support their motivation and knowledge.